2018
DOI: 10.1021/acs.est.8b00636
|View full text |Cite
|
Sign up to set email alerts
|

Light Absorption Enhancement of Black Carbon Aerosol Constrained by Particle Morphology

Abstract: The radiative forcing of black carbon aerosol (BC) is one of the largest sources of uncertainty in climate change assessments. Contrasting results of BC absorption enhancement ( E) after aging are estimated by field measurements and modeling studies, causing ambiguous parametrizations of BC solar absorption in climate models. Here we quantify E using a theoretical model parametrized by the complex particle morphology of BC in different aging scales. We show that E continuously increases with aging and stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 50 publications
8
85
2
Order By: Relevance
“…Firstly, the assumption of sphericity used in the Mie calculations to derive E sca introduces significant bias for larger BC cores with little or no coating. The resulting scattering for uncoated BC will be lower than that derived by Mie scattering due to geometrical influences as has been shown when comparing with T-matrix calculations (He et al, 2015;Wu et al, 2018), and this increases with rBC core size. Secondly, the BC at larger D c largely results from coal combustion (Sect.…”
Section: Bc Segregation By Size-resolved Mixing Statementioning
confidence: 83%
“…Firstly, the assumption of sphericity used in the Mie calculations to derive E sca introduces significant bias for larger BC cores with little or no coating. The resulting scattering for uncoated BC will be lower than that derived by Mie scattering due to geometrical influences as has been shown when comparing with T-matrix calculations (He et al, 2015;Wu et al, 2018), and this increases with rBC core size. Secondly, the BC at larger D c largely results from coal combustion (Sect.…”
Section: Bc Segregation By Size-resolved Mixing Statementioning
confidence: 83%
“…When emitted to the surroundings, BC particles transform their morphology from fractal to spherical and then grow as fully compact particles with other components depositing on the BC aerosol (Peng et al, 2016). The variation in the shapes of BC aerosols, together with the variation in the mixing states, can lead to substantial changes in aerosol optical properties (Liu et al, 2017;China et al, 2013;Wu et al, 2016Wu et al, , 2018. BC aerosols also have a significant influence on the climate by interacting with clouds (Koch and Del Genio, 2010;Roberts et al, 2008;Stevens and Feingold, 2009), ice and snow (Bond et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, debate exists among researchers. For instance, several studies (Lack et al, 2012;Wang et al, 2014Wu et al, 2016) observed a large absorption enhancement of rBC caused by mixing with the coating material, whereas other studies found negligible absorption enhancement (Cappa et al, 2012;Lan et al, 2013). Liu et al (2017) proposed that the mixing structure of rBCcontaining particles depended on the proportion of coating material.…”
mentioning
confidence: 99%